ALMA as a Redshift Machine: Using [C ii] to Efficiently Confirm Galaxies in the Epoch of Reionization - Sander Schouws; Rychard Bouwens; Renske Smit; Jacqueline Hodge; Mauro Stefanon; Joris Witstok; Juliëtte Hilhorst; Ivo Labbé; Hiddo Algera; Leindert Boogaard; Michael Maseda; Pascal Oesch; et al. (The Astrophysical Journal, 2023)
The [C ii ] _158 _μ _m line has long been proposed as a promising line to spectroscopically confirm galaxies in the epoch of reionization. In this paper, we present the results of new ALMA observations spectral scanning for [C ii ] in six particularly luminous Lyman-break galaxies at z ∼ 7. The six sources were drawn from a sample of bright z ∼ 7 galaxies identified using the wide-area optical, near-IR, and Spitzer/IRAC data over the COSMOS/UltraVISTA field and were targeted on the basis of tight constraints on their redshifts from their IRAC [3.6]–[4.5] colors. We detect significant (>9 σ ) [C ii ] lines in three of our six targets (50%) cospatial with the rest-UV emission from the ground/space-based near-IR imaging. The luminosities of the [C ii ] lines lie in the range 5.6–8.8 × 10 ^8 L _⊙ , consistent with the local [C ii ]–SFR relation. Meanwhile, their [C ii ]/ L _IR ∼ 1–3 × 10 ^−3 ratios are slightly elevated compared to local ( U )LIRGS. This could be due to lower dust-to-gas or dust-to-metal ratios. We also find that our sources display a large kinematic diversity, with one source showing signs of rotation, one source a likely major merger, and one dispersion-dominated source that might contain a bright star-forming clump. Our results highlight the effectiveness of spectral scans with ALMA in spectroscopically confirming luminous galaxies in the epoch of reionization, something that is being be applied on a significantly larger sample in the ongoing REBELS large program.